Isolation and Partial Characterization of a Dihydrochalcone From Amomum subulatum and Antimicrobial Activity of the Aqueous Extract - Karim, Mohamed Abdel; E., Naima,; O, Dalia, (IJRDO-Journal of Applied Science, 2018)
Amomum subulatum has been used since ancient times as spice . It is a herb,  widely cultivated for its economic  value. Amomum subulatum is astringent, stomachic, alexipharmic and stimulant. The oil is used traditionally against a wide array of human disorders.In this study the fruits of Ammomum sublatum were extracted with ethanol . A Silica gel TLC plates eluted with chloroform:methanol gave a chromatographically  pure component – compound I .The structure of this compound has been elucidated via its spectral data. The aqueous extract of Ammomum subulatum fruits was assessed for antimicrobial activity against five standard bacteria. The extract showed significant activity against  the bacterial strains : Pseudomonas aeruginosa  and Bacillus subtilis . It also showed good anticandidal activity.